2015
DOI: 10.1242/dev.126318
|View full text |Cite
|
Sign up to set email alerts
|

Evf2 lncRNA/BRG1/DLX1 interactions reveal RNA-dependent chromatin remodeling inhibition

Abstract: Transcription-regulating long non-coding RNAs (lncRNAs) have the potential to control the site-specific expression of thousands of target genes. Previously, we showed that Evf2, the first described ultraconserved lncRNA, increases the association of transcriptional activators (DLX homeodomain proteins) with key DNA enhancers but represses gene expression. In this report, mass spectrometry shows that the Evf2-DLX1 ribonucleoprotein (RNP) contains the SWI/SNFrelated chromatin remodelers Brahma-related gene 1 (BR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 73 publications
5
69
0
Order By: Relevance
“…Several cases of co-expression of genic lncRNA-mRNA pairs in an antisense orientation have been reported, and the modes of action of such lncRNAs on the regulation of mRNA loci are multiple and complex [11, 5154]. Strikingly, we found that the significant correlations between lncRNA and mRNA levels are positive.…”
Section: Resultsmentioning
confidence: 52%
“…Several cases of co-expression of genic lncRNA-mRNA pairs in an antisense orientation have been reported, and the modes of action of such lncRNAs on the regulation of mRNA loci are multiple and complex [11, 5154]. Strikingly, we found that the significant correlations between lncRNA and mRNA levels are positive.…”
Section: Resultsmentioning
confidence: 52%
“…Further studies revealed that Evf-2 exists in a complex with DLX1 and the BRG1 chromatin-remodeling factor. Evf-2 inhibits BRG1 activity, thereby providing a mechanism through which a lncRNA can exert a repressive effect while forming a complex with transcriptional activators [72]. These data demonstrate that the lncRNA Evf-2 can recruit both activators and repressors to the Dlx5/6 locus, and highlights the importance of using genetic knockout strategies to complement in vitro knockdown experiments in cell culture.…”
Section: Lncrnas Associated With Homeobox Transcription Factorsmentioning
confidence: 96%
“…One of the more thoroughly analyzed lncRNAs that regulates brain development is Evf2 ( Dlx6as1 ) [87, 151153]. Evf2 is expressed in the Shh-responsive cells of the ventral telencephalon during embryonic development and is transcribed from a region that partially overlaps ei, one of the two ultra-conserved enhancers (ei + eii) for the neighboring genes Dlx5 and Dlx6 [87].…”
Section: 3 Lncrna Function In Nervous System Developmentmentioning
confidence: 99%